Pelatihan Dan Pendampingan Penyusunan Modul Ajar Bagi Guru Madin Al-Qodiri Jember - Muhamad Ansori (LP3M IAIFA Kediri, 2026)
This community service program aims to improve teachers’ competence in preparing teaching modules at Madrasah Diniyah Al-Qodiri Jember. The issue identified was the absence of structured lesson planning, resulting in less effective and unprogrammed learning processes. This program employed the Participatory Learning and Action (PLA) approach through training, mentoring, discussion, and reflective evaluation. The participants consisted of 35 ustadz and ustadzah. The results indicate that 100% of participants demonstrated high motivation, 79.15% showed improved understanding of teaching module preparation, and 73% were able to independently develop teaching modules. The program contributed to strengthening pedagogical competence and fostering structured learning planning. This activity supports sustainable teacher development and enhances the quality of non-formal Islamic education institutions.